Application of a Noncarboxylated Dye Compound in a Dye-Sensitized Solar Cell Containing a Cyclodextrin Layer - Tatsuya Takeshita; Takao Umeda; Noriaki Oonishi; Michihiro Hara (International Journal of Photoenergy)
We report the fabrication and characterization of a dye-sensitized solar cell containing a carboxymethyl-β-cyclodextrin sodium salt (CM-β-CD) layer and a noncarboxylated dye compound (tris(2,2′-bipyridyl)ruthenium(II)dichloride hexahydrate (Ru-dye)). The values of the incident photon-to-current conversion efficiency (IPCE) of the Ru-dye/CM-β-CD-containing device measured under 450 and 490 nm light irradiation were, respectively, 2.35% and 3.33%. The IPCE was due to the absorption of Ru-dye in ethanol solution. In contrast, the IPCE of the device that was prepared without the CM-β-CD layer measured under 450 nm irradiation was approximately three times smaller. Accordingly, the current findings demonstrate the application of a noncarboxylated dye compound in DSSCs incorporating a CM-β-CD layer.